Penguatan Perilaku Hidup Bersih dan Sehat (PHBS) sebagai Upaya Peningkatan Derajat Kesehatan Anak Usia Dini di PAUD Az-Zahra - Fajriani, Laksmi Nur; Ariani, Farida; Solehah, Novia Zuriatun; Ardian, Junendri; Jauhari, M. Thontowi (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2024)
Abstract: Clean and healthy living behavior in Early Childhood Education institutions is a positive behavior that prevents disease, improves and maintains health, and is active in maintaining a healthy environment at school independently. Based on this, counseling on PHBS is considered very important to be carried out, as it aims to provide children with knowledge, understanding, and experience about healthy living behavior. The activity was implemented by educating people about clean and healthy living behavior and how to wash their hands properly and correctly. Before the community service activity, it was known that many children did not understand and apply clean and healthy living behavior in their daily lives. This activity showed that children at PAUD Az-Zahra could realize the importance of clean and healthy living behavior, practice washing hands properly, and understand some basic behaviors of clean and healthy living in everyday life. In addition, schools can also optimize the implementation of clean and healthy living behavior to maintain the health of early childhood.